Ethical and Legal Issues of Interaction between a Defence Lawyer and a Prosecutor during the Criminal Trial - Bondar, Volodymyr S. (2022)
The institutions of the prosecution and defence are recognised as equitable related institutions that facilitate the activities of the judiciary. The consolidation of the new status of the institution of defence in the judicial system necessitates the study of new forms of communication between the defence and the court, the principles of such interaction, including the consideration of international standards and European experience. The novelty of the study is determined by the fact that interaction between a defence lawyer and a prosecutor can only be within the framework of a court session and any exchange of information can be performed only if full publicity is achieved in the process of interaction between a defence lawyer and a prosecutor. The authors show that interaction is carried out through a judge and is completely personalised. Accordingly, the interaction should be implemented to influence the judge in the process of forming and passing an appropriate judgement. The authors determine that the such a judgement can be formed in the course of communication and the provision of certain arguments that a defence lawyer cannot communicate in advance and which can only be voiced during a court session. The practical significance of the study lies in the possibility of innovating the activities of a defence lawyer and increasing the appropriate level of perception on the part of the judge and, accordingly, the prosecutor as representatives of the institutions of justice